Innovation of Fisheries Cultivation in Pasuruan, East Java - Budi Sohibul Hayat; Adi Suhendra (Inovbook Publications, 2021)
The Indonesian government made a new policy which was stated in Government Regulation no. 38 of 2017 concerning regional innovation aims to improve the performance of local government administration. In order to achieve the objectives as intended, the target of regional innovation is directed at accelerating the realization of public welfare through improving public services, empowerment and community participation and increasing regional competitiveness. One of the regional innovations that has become a national priority is Maritime Affairs and Fisheries. This is also in line with one of the visions and missions of the President and Vice President, namely the Realization of a Prosperous Marine and Fisheries Community and Sustainable Marine and Fisheries Resources. So that the marine sector in the regions needs to be developed. One of the areas with marine and fisheries potential is Pasuruan Regency, East Java. The Pasuruan Regency Government, which knows the marine and fisheries potential of its area, needs to support this potential by making programs or innovations to accelerate the development of coastal areas. So this research was conducted to identify the effectiveness of programs or innovations carried out by the Pasuruan Regency government. The fishery innovation in Pasuruan Regency in the form of Mina has been regulated in a regional law, because it has a high potential for the welfare of its people. And from these sources, the Government has developed a number of mini innovations, such as spawning concrete pond tilapia for mass production of superior tilapia, making new mina systems or technologies, even integrating fisheries with agriculture through mina rice cultivation. These innovations are expected to improve the welfare and economy of the people of Pasuruan Regency, East Java. This study used descriptive qualitative method. The results of this study found that Pasuruan Regency has high marine and fisheries potential. The innovations and programs carried out by the Pasuruan Regency Government provide a lot of advantages and results, where it can not only produce the fishery sector, but can also get results from rice plants grown using the mina method. Suggestions in the future, it is necessary to do further research to find out other factors beyond the factors that have been done in research on the adoption of fisheries business innovation in Pasuruan Regency.